PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN PENGOLAHAN TALAS MENJADI KRIPIK DI KELURAHAN KELAISI TIMUR KABUPATEN ALOR - Hermayanti Hermayanti (JOURNAL OF COMMUNITY DEDICATION, 2025)
This community service activity aims to empower the community of Kelaisi Timur Village, Alor Regency, through training on processing taro into flavored chips to increase the added value of local products and household farmers’ income. The program was implemented using the Asset-Based Community-Driven Development (ABCD) method with five stages: inculturation, discovery, design, define, and reflection. The results show that the ABCD approach successfully mobilized community participation by utilizing local assets, especially the abundant taro commodity. Participants gained new skills, including raw material sorting, soaking taro to reduce calcium oxalate content, slicing techniques, deep-frying methods, flavoring, and packaging. The training improved technical skills, raised awareness of local potential, and established a taro chips business group committed to continuing production independently. This program is expected to enhance household income and support local food security in Kelaisi Timur.